EDUCATION 5.0: CROSS-PERSPECTIVES FROM JAPAN AND ZIMBABWE - Safae ANFOUD; Lalla Fatima Zohra ALAMI TALBI (Universitaria Publishing House, Craiova, 2024)
After the COVID-19 pandemic, the world massively embraced the transition to a digital environment, generating significant repercussions in various sectors, including education. The revolutionary technological development that has given rise to the so-called 5.0 industry represents a turning point that calls for a revision of the global economic development model, basing it henceforth on knowledge instead of industry. The concept of Education 5.0 has emerged in this context to offer a humanized education centered on the learner, fostering his or her social and emotional development, and based on the use of advanced technologies such as artificial intelligence and the Internet of Things (IoT). This educational model, recommended by organizations such as UNESCO and UNICEF, promotes a holistic, multidimensional approach to learning, aimed at training responsible citizens and workers. This study examines the adoption of Education 5.0 in the context of a developed country, Japan, and a developing country, Zimbabwe, using a comparative approach. This is based on an analytical grid assessing learning performance, learner well-being and the acquisition of work values. By analyzing feedback from these two countries, this study aims to better understand how Education 5.0 can be adapted to different contexts to meet the needs of the knowledge economy and society.